Measurement on strain rate sensitivity properties of rice husk/ linear low density polyethylene (LLDPE) composites under various loading rates - Nur Suhaili Abdul Wahab (School of Materials Engineering, 2016)
The scope of this study is to investigate the effect of strain rates on the compressive properties of rice husk reinforced linear low density polyethylene composites under static and dynamic loading. Five different compositions of RH/LLDPE composites will be prepared and mixed using twin screw extruder. Then, the specimens will be compacted using hot press machine. The sample will be compressed under three different strain rates loading at both static and dynamic loading, respectively. Besides, the effect of surface treatment and particle sizes of RH/LLDPE composites under both static and dynamic loading also will be investigated. The specimens will be characterized using Fourier Transform Infrared (FTIR) for compound identification and Scanning Electron Microscopy (SEM) for morphology study. At the end of this study, the compressive properties, strain rate sensitivity and thermal activation volume of the composites are analyzed based on the effect of strain rates toward filler contents, surface treatment and particle sizes.